2013
DOI: 10.1590/s1516-35982013001000009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of addition of fluorine in diets differing in protein content on urinary fluoride excretion, clinical chemistry and thyroid hormones in calves

Abstract: -In order to compare the effects of addition of fluorine (F) in diets differing in protein content on the urinary F excretion, blood profile and thyroid hormones, 30 crossbred calves (6-8 months) initially exposed to different protein levels were allotted into six groups in a 3 × 2 factorial design. The factors included three different levels of protein: normal (NP; 100%), low (LP; 75%), and high (HP; 125%) besides two levels of supplemental fluorine (as sodium fluoride) at 0 or 200 mg/kg diet. The animals wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…This substantial presence of crude proteins holds significance as it suggests Spirulina platensis may contribute to overall protein intake in animals. This aspect potentially plays a role in mitigating the adverse effects of fluoride toxicity on protein synthesis 43 , 44 . Furthermore, the findings of the current study revealed that the fluoride excretion level via feces was the same in all studied groups.…”
Section: Discussionmentioning
confidence: 99%
“…This substantial presence of crude proteins holds significance as it suggests Spirulina platensis may contribute to overall protein intake in animals. This aspect potentially plays a role in mitigating the adverse effects of fluoride toxicity on protein synthesis 43 , 44 . Furthermore, the findings of the current study revealed that the fluoride excretion level via feces was the same in all studied groups.…”
Section: Discussionmentioning
confidence: 99%